(untitled) (Research, Society and Development, 2022)
Objectives: To Map and describe the activities and risks of a surgical process in a specialized hospital, and propose strategies for patient safety through a risk management proposal. Methodology: Qualitative research, in the form of action research, carried out with 12 professionals working in a surgical center of a specialized hospital in northwestern São Paulo, from May to June 2017. Brainstorming tools were used to understand the internal flow, Business Process Model and Notation and Supplier, Input, Process, Output and Customer for process mapping, National Health Agency’s Risk Matrix for risk stratification and improvement proposals, the methodology proposed by the Institute of Healthcare Improvement. Results: In the mapping, the operating room was divided into admission; operating room and anesthetic recovery, which resulted in 13 processes and 42 activities described. It was possible to observe relevant interactions with administrative and support processes. 42 risk situations were identified; 31.8% were classified as medium risk, 43.1% high and 25.0% extreme, which generated 87 proposals for interventions to improve patient safety. Conclusion: Mapping the activities and risks of surgical processes provides the manager with tools for decision making; above all, the adoption of corrective strategies for each of the risk points in the flow of patient care.